The Importance of Educators’ Creativity in Encouraging Community Learning Participation - Adibah Feikha Naylah; Patricia Romasta Hutabalian; Wulan Sari; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the importance of educator creativity in increasing community learning participation in non-formal education. The approach used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that educator creativity plays a significant role in creating a learning environment that is engaging, contextual, and relevant to community needs. This creativity is reflected in learning methods, media use, and interpersonal approaches that can increase student motivation and engagement. Furthermore, community learning participation increases when learning is designed flexibly and applicably. However, obstacles remain, such as limited facilities and educator competencies. Therefore, continuous strengthening of educator creative competencies is necessary to improve the quality of community education.